Insecticides Used in the Urban Environment: Mode of Action - S.M. Valles; P.G. Koehler (EDIS)
This document explains the modes of action of various insecticides used in urban environments. It categorizes insecticides based on their effects on the nervous system, energy production, cuticle production, endocrine system, and water balance. The article details how different chemicals, such as pyrethroids, carbamates, and organophosphates, disrupt insect physiology, leading to toxicity and death. It also highlights the specific mechanisms through which these insecticides operate, providing a comprehensive understanding of their biological impacts. First publication date: September 1997.